Access to reproductive health services among the female floating population of childbearing age: a cross-sectional study in Changsha, China - Yanhui Zhou; Ting Wang; Jingxia Fu; Mingzhu Chen; Yanting Meng; Yang Luo (BMC, 2019)
Abstract Background The floating population serves an important role in economic and social development. However, little is known about the floating population's reproductive health (RH) services, especially in low- and middle-income countries. This study aimed to assess the use of reproductive health services in the female floating population in China, which is a country with the largest floating population in the world. Methods A cross-sectional survey was conducted for more than 3 months. Six hundred twenty females of childbearing age in a floating population were recruited into the study by using random sampling, with these individuals being recruited from six community centres in Changsha, China. The use of reproductive health services was assessed by utilizing a self-designed questionnaire. Results A total of 555 participants returned the completed questionnaires (effective response rate of 89.5%), including 405 married women and 150 unmarried women. The utilization of RH services was poor in individuals who could access RH policies (39.3%), RH education (36.4%), RH counselling (27.4%), gratis contraceptives (36.0%), and free RH examinations (38.9%), and married women utilized these services at higher rates than unmarried women (P < 0.01), although 63.3% of the unmarried women had sexual lifestyles. The marital status was significantly associated with receiving RH education, RH counselling, gratis contraceptives, and free RH examinations. Age was significantly associated with the use of RH education and free RH examinations. The average personal monthly income had a significantly beneficial effect on the use of free RH examinations. Obstetrics and gynaecological disease prevention (67.2%) were the greatest needs of the RH services, and the use of the Internet was the best way to obtain these services. Most of the individuals (77.3%) hoped to receive gynaecological health screenings that were provided by obstetrics and gynaecology hospitals. Conclusions The female floating population exhibited poor awareness of RH and rarely used RH services, especially in unmarried women. The results suggest that educational interventions for the female floating population, as well as policy and resource developments should meet the demands for RH services, which are urgently needed in China.